The trifecta of violence: a socio-historical comparison of lynching and violence against transgender women - Lenning, Emily (Critical criminology, 2021)
This article explores violence against transgender women—from the state control of trans bodies through laws and policies to an apparent increase in transphobic murders in the United States (US). Using a socio-historical comparison to the legacy of racism, racist policies, and lynching in the US, we consider the relationship between hateful rhetoric, state-sanctioned discrimination, such as North Carolina’s Public Facilities Privacy and Security Act (known as "House Bill 2" or "HB2"), and the recently reported uptick in the murders of transgender women of color. Given the feminist backlash and racial threat rhetoric that characterizes the current political landscape, an exploration into this link is crucial to understanding the extreme threats facing transgender women.